Analyzing the Sustainability of Current Account in ASEAN Countries: Test of Intertemporal Borrowing Constraints - Kalyoncu, Huseyin; Kaplan, Muhittin (International Journal of Economics and Financial Issues, 2014)
The objective of this paper is to investigate the sustainability of current account imbalances by using the data of five ASEAN countries, namely, Indonesia, Malaysia, Philippines, Singapore and Thailand over the 1981-2008 periods. Sustainability of current account for ASEAN countries is analyzed under intertemporal borrowing constraint (IBC) approach by performing an empirical analysis of Pedroni (1999) panel cointegration between exports and imports plus net transfer payments plus net interest payments. The empirical results of panel cointegration test show that these variables are cointegrated for whole period and two sub-periods. To find regression coefficient we use panel FMOLS and DOLS estimators. It is found that the coefficient is not significantly equal to one but very close to one. The overall results provide evidence in favour of the sustainability of the current account for five ASEAN countries as a group. Keywords: panel data unit-root test; current account; solvency JEL Classifications: C23; F30; F32